Synthesis, Characterization and Urease Inhibiting Derivatives of 5-(3,4-Methylenedioxyphenyl)-1,3,4-Oxadiazol-2-thiol - Akhtar, Muhammad Nadeem (Asian J. Chem, 2014)
In the present work, the urease inhibition activity of 1,3,4-oxadiazole bearing molecules was evaluated and were found to be potential inhibitors. 3,4-(Methylenedioxy)benzoic acid (1) was employed to synthesize 5-(3,4-methylenedioxyphenyl)-1,3,4-oxadiazol-2-thiol (4) via a series of steps. It was further stepped to yield S-substituted-5-(3,4-methylenedioxyphenyl)-1,3,4-oxadiazole derivatives (6a-h) on reaction with alkyl/aralkyl halides (5a-h) in DMF using LiH as an activator. All the synthesized compounds were well supported by IR, 1H NMR and EIMS spectral analysis. The enzyme inhibition activity against urease enzyme showed these molecules as potent inhibitors of this enzyme. - See more at: http://www.asianjournalofchemistry.co.in/(X(1))/user/journal/viewarticle.aspx?ArticleID=26_16_15#sthash.Y6WNhFR2.dpuf